INFLUENCE CONSERVATISM ACCOUNTING, COMPANY SIZE , LEVERAGE, CAPITAL STRUCTURE AND PROFITABILITY AGAINST THE EARNING RESPONSE COEFFICIENT - Krisno Simatupang; Maduri -; Novalina Sinaga; Agnes D.T Hutagaol; Nintha Katharina; Umi Kalsum (Jurnal Ipteks Terapan, 2023)
Objective main study between 2016 and 2020 , research This done so Can know impact period long from a number variable influencing finance price share producing company food And drink And listed on the Indonesia Stock Exchange . Data is collated from 2016-2020 using 10 businesses choice of the total population of 24 and analyzed using SPSS 26. Analysis produce estimate coefficient 20 ,5, there will be a 29.9 percent increase on price share producing company food And drink between in 2016 and 2020, as determined by Current Ratio, Return on equity, Earning per share, and Debt to Equity Ratio , and enhancement share by 70.1 percent price company let variable the open . Findings from discussion indicates that the influence is beneficial And Enough big to price generated by a combination of CR, ROE, EPS, and DER. Please , some CR and DER do not affect price company , but ROE and EPS matter .